Visual study of mass transfer characterization in the process of biological catalytic hydration of acrylonitrile using pendant drop method. Issue 96 (17th October 2015) - Li, Jiahui; Yang, Lufan; Ding, Xifeng; Chen, Jie; Wang, Yujun; Luo, Guangsheng; Yu, Huimin
<x xml:space="preserve">Abstract</x> In this work, a pendant drop method was utilized to observe visually the mass transfer process of an acrylonitrile droplet during bio-hydration.